2005
DOI: 10.1002/dc.20201
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mesothelioma from adenocarcinoma in serous effusions: The role of hyaluronic acid and CD44 localization

Abstract: Differentiating cells of mesothelial origin from adenocarcinoma (ACA) based on morphology alone can be a diagnostic challenge, especially in cytological specimens. Malignant mesothelioma (MM) is characterized by accumulation of abundant intracellular hyaluronic acid (HA), a feature that is not reported in ACA. The purpose of this study was to evaluate the significance of cellular HA using an HA-specific binding peptide (HABP) and the expression of its principal receptor, the standard CD44 molecule (CD44S). Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Such errors in diagnosis usually are caused by misinterpretation of adenocarcinoma cells as reactive mesothelial cells. 9 The rate of false positive diagnoses also is significant and often caused by overinterpretation of reactive mesothelial cells as malignant cells. 5 ICC can greatly aid in such diagnostic dilemmas, but, currently, available markers have varying sensitivities and specificities for mesothelial cells or cells of epithelial differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Such errors in diagnosis usually are caused by misinterpretation of adenocarcinoma cells as reactive mesothelial cells. 9 The rate of false positive diagnoses also is significant and often caused by overinterpretation of reactive mesothelial cells as malignant cells. 5 ICC can greatly aid in such diagnostic dilemmas, but, currently, available markers have varying sensitivities and specificities for mesothelial cells or cells of epithelial differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Many studies have reported the use of different immunocytochemical panels comprising various antibodies in the differential diagnosis between reactive mesothelial, adenocarcinoma, and malignant mesothelioma cells in serous effusions. 13,29,30 Some authors reported about the role of DNA-ICM (DNA-ploidy) in effusion cytology. The results have shown that nonmalignant mesothelial lesions (reactive mesothelial proliferations) were all DNAdiploid or -polyploid, and all DNA-aneuploid lesions in contrast corresponded to malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recent studies have indicated that hyaluronan can also exist intracellularly, however, the intracellular functions of hyaluronan are unknown. 17 Chondroitin has a structure similar to that of hyaluronan in which the 2-acetamido-2-deoxy-D-glucopyranose residue of hyaluronan is replaced with a 2-acetamido-2-deoxy-D-galactopyranose residue.…”
Section: Introductionmentioning
confidence: 99%